Faktor-Faktor Yang Mempengaruhi Tingkat Stres Akademik Mahasiswa Semester Akhir Di Fakultas Ilmu-Ilmu Kesehatan Universitas Abulyatama - Urip Pratama; Nurul Amna; Barjan Arif (STIKes Ibnu Sina Ajibarang, 2023)
University students are vulnerable to experience stress due to academic burden and final assignments overload. Thus, the pressure to finish academic paper on time leads to stress in their final-year study. There are two main factors that cause academic stress: internal and external factors. This study aims to determine the influence of internal and external factors toward the academic stress level. This study used a cross-sectional design with a sample of 67 final-semester students as respondents chosen using total sampling technique. The study conducted from June 6th - 17th, 2023. The result of data analysis using the Chi-Square test shows that 43 respondents experience severe stress (64, 2%), positive internal factors 27 respondents (40, 3), and external factors 37 respondents (55, 2). It indicates there is the influence of positive internal factors (P-value 0,002) and the negative external factors (P-value 0,003) on academic stress. Thus, internal and external factors influence the academic stress level of the final-semester students Faculty of Health Sciences, Abulyatama University. This study suggests the final-semester students consult the consultation officers to find best solution when experiencing stress. They can go for consultation to reliable persons, always positive thinking, and practice relaxation techniques by taking a deep breath.